The Appearance of Antiphage Antibodies in Sera of Patients Treated with Phages - Marzanna Łusiak-Szelachowska; Beata Weber-Dąbrowska; Maciej Żaczek; Ryszard Międzybrodzki; Andrzej Górski (Antibiotics)
Background: Bacteriophages are neutralized by the sera of patients undergoing phage therapy (PT), particularly during local or concomitant local and oral phage administration in bone infections, soft tissue infections, or upper respiratory tract infections. Methods: The antiphage activity of the sera (AAS) level of 27 patients with bacterial infections such as bone infections, soft tissue infections, or upper respiratory tract infections undergoing PT was performed using the plate phage neutralization test. Results: Our preliminary results suggest that high levels of antiphage antibodies appear late in the treatment period, at the earliest in the 3rd–8th week of PT. Patients with bone infections treated locally with the S. aureus phage Staph_1N and patients with upper respiratory tract infections administered locally and orally with the S. aureus phage Staph_A5L had elevated levels of antiphage antibodies in sera during PT. In parallel to these results, it has been shown that a strong antiphage humoral response does not prevent a positive outcome of phage treatment. Conclusions: The earliest time point at which high levels of antiphage antibodies in sera appear during local and oral PT is day 21 of therapy. We noticed that the high level of antiphage antibodies in sera occurring during local or both local and oral PT was correlated with the type of infection and phage type.